Critical analysis of the relationship between imposex and butyltin body burden in Nassarius reticulatus and Nucella lapillus. (June 2018) - Rial, D.; Bellas, J.; Ruiz, J.M.
Abstract: Imposex is a disorder caused by organotins, mainly tributyltin, which results in the appearance of male sexual characteristics in females of gastropod mollusks. The main objective of this work was to make a critical analysis of the relationship between imposex and butyltin body burdens in Nucella lapillus and Nassarius reticulatus . Specifically, this study evaluates possible additive effects among butyltins, proposes scales of effects based on robust statistical criteria as alternatives to existing ones and defines the body burdens of TBT in N. lapillus and N. reticulatus corresponding to the assessment classes (ACs) of the Vas Deferens Sequence Index (VDSI) established by OSPAR. Data of organotin body burdens and biological effects was retrieved from the ICES Dataset and from scientific literature. All responses, except the percentage of females displaying Imposex (IMPF) in Nucella lapillus, showed a sigmoidal profile regarding to the body burden of mono- (MBT), di- (DBT) and tributyltin and sum of butyltins (SumBTs). TBT and the SumBTs were better indicators of the VDSI or Relative Penis Size Index/Relative Penis Length Index (RPSI/RPLI) responses than MBT or DBT in most cases. From a statistical point of view, RPSI/RPLI and VDSI were better indicators of contamination by TBT than IMPF, although both RPSI and RPLI showed lower sensitivity than VDSI. The model used for describing the joint effect of butyltins provided a statistically significant fitting to the data assuming a null effect for both MBT and DBT for N. lapillus, and a lower toxic contribution of MBT and DBT with respect to TBT for N. reticulatus . RPSI or RPLI values, equivalent to the ACs for VDSI, were proposed as alternative criteria when measuring moderate to high levels of imposex. TBT concentrations in N. reticulatus and N. lapillus tissues, corresponding to the ACs were calculated and provided valuable information for cross-species comparisons. Graphical abstract: Image 1 Highlights: The relationship between imposex and butyltin concentrations was analysed. Data was retrieved from ICES Dataset and scientific literature. The overall response profile observed for RPSI/RPLI or VDSI was sigmoidal. Robust statistical criteria as alternatives to existing ones were proposed. TBT concentrations corresponding to the assessment classes were calculated. Abstract : TBT concentrations in N. reticulatus and N. lapillus tissues, corresponding to the ACs were calculated and provided valuable information for cross-species comparisons.